Konsep Pendidikan dalam Pemikiran Ibnu Khaldun: Integrasi Ilmu dan Akhlak - Yaman, Nur; Yadi, Yadi; Mulyanto, Mulyanto (Lembaga Yasin AlSys, 2025)
This study examines Ibn Khaldun’s views on education, particularly the integration of knowledge and character formation. Using a descriptive qualitative approach through literature review, the study finds that Ibn Khaldun regarded education as a process of shaping the whole person, encompassing intellectual, spiritual, and moral dimensions. He emphasized the importance of gradual learning (tadarruj), the cultivation of habitual values (malakah), teacher role modeling, and the rejection of coercive teaching methods. According to him, education should be adapted to the developmental stages of learners, integrating ʿaqliyyah (rational sciences) and naqliyyah (religious sciences) in a balanced manner. This concept is relevant to contemporary educational needs that prioritize holistic approaches and character building. The findings indicate that Ibn Khaldun’s educational thought holds great potential for shaping a more meaningful modern Islamic education system.